A Double Atomic‐Tuned RuBi SAA/Bi@OG Nanostructure with Optimum Charge Redistribution for Efficient Hydrogen Evolution. (14th February 2023) - Zhao, Xiaole; Wu, Geng; Zheng, Xusheng; Jiang, Peng; Yi, Jun‐dong; Zhou, Huang; Gao, Xiaoping; Yu, Zhen‐Qiang; Wu, Yuen
Abstract: Charge redistribution on surface of Ru nanoparticle can significantly affect electrocatalytic HER activity. Herein, a double atomic‐tuned RuBi SAA/Bi@OG nanostructure that features RuBi single‐atom alloy nanoparticle supported by Bi−O single‐site‐doped graphene was successfully developed by one‐step pyrolysis method. The alloyed Bi single atom and adjacent Bi−O single site in RuBi SAA/Bi@OG can synergistically manipulate electron transfer on Ru surface leading to optimum charge redistribution. Thus, the resulting RuBi SAA/Bi@OG exhibits superior alkaline HER activity. Its mass activity is up to 65000 mA mg −1 at an overpotential of 150 mV, which is 72.2 times as much as that of commercial Pt/C. DFT calculations reveal that the RuBi SAA/Bi@OG possesses the optimum charge redistribution, which is most beneficial to strengthen adsorption of water and weaken hydrogen‐adsorption free energy in HER process. This double atomic‐tuned strategy on surface charge redistribution of Ru nanoparticle opens a new way to develop highly efficient electrocatalysts. Abstract : A double atomic‐tuned RuBi SAA/Bi@OG nanostructure was prepared by one‐step pyrolysis method. The electron density on surface of Ru nanoparticle can be synergistically modulated by alloyed Bi single atom and adjacent Bi−O single site leading to optimum charge redistribution. Thus, the resulting RuBi SAA/Bi@OG exhibits superior alkaline HER activity.